Henoch-Schönlein Purpura and Elevated Hepatitis C Virus Antibody in a Girl With Nasopharyngeal Diffuse Large B-Cell Lymphoma - Jen-Yin Hou; Hsi-Che Liu; Der-Cherng Liang; Yin-Sum Choi; Chia-Ying Lin; Ting-Chi Yeh (Pediatrics and Neonatology)
Henoch-Schönlein purpura (HSP) or hepatitis C virus (HCV) infection was reported in association with malignancies. However, HSP and HCV infection rarely present in pediatric patients with non-Hodgkin’s lymphoma. We describe an 8-year-old girl with Stage-IV diffuse large B-cell lymphoma who presented with HSP and elevated HCV antibody titer at diagnosis and at relapse. After treatment, purpura disappeared and HCV antibody titer returned to normal range. There was no recurrence of HSP or elevated HCV antibody during a follow-up of 2 years.